A case of upper gastrointestinal acute bleeding as a complication of renal carcinoma metastases to the papilla Vateri - Śmigielski, Jacek; Piskorz, Łukasz; Wawrzycki, Marcin; Jabłoński, Sławomir; Brocki, Marian (Contemporary Oncology/Współczesna Onkologia, 2013)
Acute bleeding from metastatic tumour of the papilla Vateri is an extremely rare case. In this report the case of a woman who suffered from complications after a metastatic tumour of the papilla is described. Seventeen years following resection of the kidney due to clear cell carcinoma the patient was admitted to the clinic because of massive bleeding (Forrest IB) to the upper digestive tract in the form of sanguineous vomiting. The conducted diagnostics revealed a bleeding tumour of the papilla Vateri. Endoscopic treatment could not effectively stop the bleeding. A surgical procedure was performed by Whipple’s method. A histopathological examination showed a metastatic clear cell tumour of the kidney. The patient was discharged from hospital on the 8th day following her admission and was also referred for further oncological treatment. The discussion is based on other cases of rare bleeding from the digestive tract within tumours of the bile duct and papilla Vateri.